Latency period of aristolochic acid-induced upper urinary tract urothelial carcinoma - Jhuang, Jing-Rong; Chiu, Po-Chun; Hsieh, Tung-Che; Chen, Chung-Hsin; Pu, Yeong-Shiau; Lee, Wen-Chung (Frontiers in Public Health, 2023)
Purpose: Aristolochic acid (AA) is a carcinogen in upper urinary tract urothelial carcinoma (UTUC). This study investigated the latency period between AA exposure and UTUC development. Materials and Methods: This population-based cohort study was designed using record linkage of the National Health Insurance Research Database (NHIRD), Taiwan Cancer Registry Dataset, and cause-of-death data in Taiwan. Those aged 40–79 years were enrolled in this study. Patients who died or had renal insufficiency or UTUC before 2005 were excluded. The doses of AA exposure and rates of comorbidities between 2000 and 2005 were obtained. The Cox proportion hazard model was used to estimate the risk of UTUC between 2005 and 2016. In addition, the Cox model with time-varying coefficient of AA was used to measure the latency period of UTUC. Results: Of the 752,232 participants enrolled from the NHIRD, 520,871 (68.29%), 210,447 (27.59%), and 31,415 (4.12%) were exposed to cumulative AA doses of 0–1 mg, 1–150 mg, and >150 mg, respectively. A total of 1,147 (0.15%) patients were diagnosed with UTUC between 2005 and 2016. The latency periods of UTUC in middle-aged (40–59 years old) men with cumulative AA doses of 1-150 mg and middle-aged women with cumulative AA doses of 1-150 mg and >150 mg were 8, 9, and 7 years, respectively. Among the aged (60–79 years) individuals, no time-varying effect was observed, and the latency period could not be measured. Conclusion: A decreased risk of UTUC was observed after the ban on AA in Taiwan, especially in middle-aged women with moderate to high doses of AA exposure and men with moderate doses of AA exposure. The latency period of UTUC varies with age, the dose of AA exposure, and sex.